2011
DOI: 10.1186/ar3258
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies predate the onset of systemic lupus erythematosus in northern Sweden

Abstract: IntroductionAutoantibodies have a central role in systemic lupus erythematosus (SLE). The presence of autoantibodies preceding disease onset by years has been reported both in patients with SLE and in those with rheumatoid arthritis, suggesting a gradual development of these diseases. Therefore, we sought to identify autoantibodies in a northern European population predating the onset of symptoms of SLE and their relationship to presenting symptoms.MethodsThe register of patients fulfilling the American Colleg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
157
1
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(178 citation statements)
references
References 30 publications
11
157
1
5
Order By: Relevance
“…Whether systemic immune alterations pre‐dating disease have an effect on pregnancy is not known. Autoantibodies associated with SLE, including antiphospholipid antibodies and SSA, both of which are known to be associated with pregnancy morbidity, are present up to 5 years before the clinical diagnosis of SLE 4, 5, 6. Furthermore, as the clinical diagnosis nears, the levels of many of these autoantibodies increase 4.…”
Section: Introductionmentioning
confidence: 99%
“…Whether systemic immune alterations pre‐dating disease have an effect on pregnancy is not known. Autoantibodies associated with SLE, including antiphospholipid antibodies and SSA, both of which are known to be associated with pregnancy morbidity, are present up to 5 years before the clinical diagnosis of SLE 4, 5, 6. Furthermore, as the clinical diagnosis nears, the levels of many of these autoantibodies increase 4.…”
Section: Introductionmentioning
confidence: 99%
“…Autoantibodies can precede the full clinical expression of an underlying disease for many years 18,19 , and atypical clinical presentations of CTD can occur. Thus, clinical judgment should guide ANA testing in these cases 11 .…”
Section: Resultsmentioning
confidence: 99%
“…19 A study conducted in Northern Sweden, reported that autoantibodies can be detected in the serum of individuals who develop systemic lupus erythematosus several years before the appearance of clinical signs and symptoms. 20 Considering the association of different oral addictive habits with the development of autoimmune diseases, some researchers have reported that smoking protects against production of antithyroid peroxidase antibodies.…”
Section: Discussionmentioning
confidence: 99%